Circadian Clock Regulation of Hepatic Energy Metabolism Regulatory Circuits - Hunter, Ann Louise (Biology (Basel), 2019)
The liver is a critical organ of energy metabolism. At least 10% of the liver transcriptome demonstrates rhythmic expression, implying that the circadian clock regulates large programmes of hepatic genes. Here, we review the mechanisms by which this rhythmic regulation is conferred, with a particular focus on the transcription factors whose actions combine to impart liver- and time-specificity to metabolic gene expression.